ERGONOMIC EXERCISE AGAINST LOWERING BLOOD PRESSURE - Bagus Kurniawan (Journal of Holistic and Traditional Medicine, 2021)
Hypertension is a condition where a person's blood pressure is at above 140/90 mmHg and is a major factor for the occurrence of stroke, disease heart, kidney, and peripheral circulation problems. This hypertension disease must receive appropriate and safe treatment, the handling can be pharmacological and nonpharmacological. Pharmacological handling is the consumption of drugs while non-pharmacologically one of them is exercise (ergonomic exercise), ergonomic exercise resembles prayer movements so that it is easier to apply in life. daily and its movements are by the rules for creating the body which is inspired by the prayer movements so that it is easy for someone to do this gymnastic movement. Ergonomic exercise is good for body health because this exercise can open, clean, and activate systems in the body such as cardiovascular, urinary, and reproductive. Gymnastics can relax blood vessels. Gradually exercise ergonomics will relax blood vessels, resulting in blood pressure will decrease.